ADVANCE CARE PLANNING IN PRIMARY CARE IN THE EAST OF ENGLAND: PUTTING GUIDANCE INTO PRACTICE?. Issue 2 (1st June 2013) - Hayhoe, B; Howe, A
Abstract : Background: Advance care planning (ACP) continues to gain importance in UK healthcare, with definition in statute in the Mental Capacity Act 2005 and professional guidance advocating its use in primary care. However, the impact on clinical practice is unclear. Aim: This qualitative study investigates ACP in UK primary care, establishing current experience, ideas and views on ACP, and identifying the extent to which guidance is embedded in practice. Method: Fifteen General Practitioners and four Old Age Psychiatrists took part in semi-structured interviews. Themes arising were discussed in a lay focus group, before a questionnaire survey of 140 primary care practices tested findings in detail. Results: Many primary care physicians remain unfamiliar with guidance on ACP and lack experience in its use. However, while they feel a need for support and training, practitioners are well aware of barriers to ACP as well as potential ethical problems, and can provide relevant suggestions for improvement. Agreeing with lay people that primary care has a key role in this process, professionals express strong commitment to make more use of ACP, ensuring patients' wishes are recorded and respected. Discussion: Primary care is an ideal environment to build on conceptual understanding of ACP, translating evidence, policy and guidance into practice. Conclusion: Primary care professionals show keen interest and openness to ideas regarding ACP. These findings provide novel insight into understanding and use of ACP in primary care, with potential to facilitate development of practical strategies to enhance implementation of quality, patient centred ACP in this setting.